Implementing Question and Answer Technique to Enhance Students’ Speaking Ability at SMP Islam Paramitha Malang: Menerapkan Teknik Tanya Jawab untuk Meningkatkan Kemampuan Berbicara Siswa di SMP Islam Paramitha Malang - Adi, Adi (JEES (Journal of English Educators Society), 2016)
Speaking is one of language skills which has to be mastered by the students. By being able to speak, students will be able to transfer their thought to others. Unfortunately, sometimes students, at SMP Islam Paramitha especially, failed to utter their idea in spoken manner due to several factors as lack of vocabulary, not knowing what and how to say the ideas, and mostly feeling unconfident. This problem cannot be neglected; therefore, the researcher decided to carry out a two-cycle Classroom Action Research (CAR). In This CAR the researcher implemented question and answer technique to improve students’ speaking ability on expressing their daily activities. By using observation sheets, interview guide, and test, it was found that 70% of the students had been successfully improving their speaking ability. As a result, the intended spoken communication, either between students and students or teacher and students, did take place.